Building with Nature perspectives Cross-disciplinary BwN approaches in coastal regions - van Bergen, Janneke; Nijhuis, Steffen; Brand, Nikki; Hertogh, Marcel (RESEARCH IN URBANISM SERIES (RiUS), 2021)
This publication offers an overview of the latest cross-disciplinary developments in the field of Building with Nature (BwN) for the protection of coastal regions. The key philosophy of BwN is the employment of natural processes to serve societal goals, such as flood safety. The starting point is a systems-based approach, making interventions that employ the shaping forces of the natural system to perform measures by self-regulation. Initial pilots of this innovative approach originate from coastal engineering, with the Sand Motor along the coast of South Holland as one of the prime examples. From here, the BwN approach has evolved into a new generation of nature-based hydraulic solutions, such as mangrove forests, coastal reefs, and green dikes.